2006
DOI: 10.1108/14720700610655132
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance in Islamic perspective

Abstract: Purpose-The purpose of this conceptual paper is to develop a discussion expounding the Islamic perspective of corporate governance as a special case of a broader decision-making theory that uses the premise of Islamic socio-scientific epistemology. Islamic epistemology is premised on the divine oneness of God. The worldly explanation of divine unity is done by means of specific laws and instruments that make the Islamic epistemology functionally viable in developing, implementing and inferring from the applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(113 citation statements)
references
References 9 publications
3
105
0
5
Order By: Relevance
“…Also, another practical implication is to understand how mining companies are governing their CG and SR activities, which would be useful for managers seeking to learn from best practices. Choudhury and Hoque (2006) affirm that CG is a package of contracts and rules under which a company functions, is legitimized by legal promulgation, and is protected by the legal principles of any government and state. According to Organization for Economic Cooperation and Development (1999), CG is merely part of the larger economic context in which firms operate, which includes macroeconomic policies and the degree of competition in product and factor markets.…”
Section: Research Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, another practical implication is to understand how mining companies are governing their CG and SR activities, which would be useful for managers seeking to learn from best practices. Choudhury and Hoque (2006) affirm that CG is a package of contracts and rules under which a company functions, is legitimized by legal promulgation, and is protected by the legal principles of any government and state. According to Organization for Economic Cooperation and Development (1999), CG is merely part of the larger economic context in which firms operate, which includes macroeconomic policies and the degree of competition in product and factor markets.…”
Section: Research Gapmentioning
confidence: 99%
“…Corporate governance (CG) is related to those legal and organizational structures that look after the internal integrity of a corporation (Choudhury & Hoque, 2006). According to Soujata (2018), most respondents acknowledge the positive impact of good CG in the daily operations of their organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Corporate governance is the relationship among various participants (CEO, management, shareholders, and employee) in determining the direction and performance of corporations. It ensures that the board of directors is accountable for the pursuit of corporate objectives and that the corporation itself conforms to the law and regulations (Choudhury & Hoque, 2006). Generally, it is observed that the main objective of the corporation including the so-called Islamic corporation is to maximize the shareholder's value of wealth.…”
Section: Shariah Good Governancementioning
confidence: 99%
“…Hasan, 2010;Muneeza & Hassan, 2014). Other researchers introduce it to Islamic corporate governance (Bhatti & Bhatti, 2010;Choudhury & Hoque, 2006;Elghuweel, Ntim, Opong, & Avison, 2017). The concept has been modified because it must comply with Islamic principles.…”
Section: Introductionmentioning
confidence: 99%